Nghiên cứu khả năng xúc tác quang hóa khử màu metyl da cam của Cu2O kích thước nanomet - Nguyệt và cộng sự, Triệu Thị (Vietnam Journal of Chemistry, 2014)
The photocatalytic activity of Cu2O nano-particles was investigated by degradation reaction of methyl orange in aqueous solution under visible light (using E27 Mercury 125W lamp). The obtained results indicated that nano-sized Cu2O has good photocatalytic efficiency: the decomposition level of methyl orange reaches 75% and 84% after 2 hours and 4 hours, respectively; and the photocatalytic activity of recycled Cu2O decreased slightly after each time it was used for catalysing.